Development and implementation of a culturally tailored diabetes intervention in primary care - Osborn, Chandra Y (Springer-Verlag, 2011)
Diabetes education for ethnic minorities should address variations in values underlying motivations, preferences, and behaviors of individuals within an ethnic group. This paper describes the development and implementation of a culturally tailored diabetes intervention for Puerto Ricans that can be delivered by a health care paraprofessional and implemented in routine clinical care. We describe a formative process, including interviews with providers, focus groups with patients and a series of multidisciplinary collaborative workshops used to inform intervention content. We highlight the intervention components and link them to a well-validated health behavior change model. Finally, we present support for the intervention’s clinical effects, feasibility, and acceptability and conclude with implications and recommendations for practice. Lessons learned from this process should guide future educational efforts in routine clinical care.